(untitled) (Linguostylistic Studies, 2021)
The article highlights information about the Vth International Scientific Conference “Linguostylistics of the XXI Century: Status and Prospects” organized by the Department of the Ukrainian Language History and Culture of Lesya Ukrainka Volyn National University together with the Institute of Ukrainian Language at NAS of Ukraine and Palacký University Olomouc (Czech Republic). The topics of plenary and sectional meetings are analyzed with a focus on the hotly-debated issues of modern linguostylistics, such as theoretical achievements of the Ukrainian Linguopersonology, multifunctionality of language personality, elite language personality, interpretation of Lesia Ukrainka’s language in the 21st century, the idiolect of the modern speaker, idiosyncrasies and media discourse, onyms in individual/personal vocabulary, a translator’s individual style, and methods of studying idiosyncrasies in secondary and higher education institutions. The round-table discussions on the topic “Ukrainian Linguopersonology Tomorrow: Development Vector” outlined the prospects for further conference meetings.